2021
DOI: 10.1002/adhm.202001800
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Needle Array‐Mediated Drug Delivery Accelerates Wound Healing

Abstract: A major impediment preventing normal wound healing is insufficient vascularization, which causes hypoxia, poor metabolic support, and dysregulated physiological responses to injury. To combat this, the delivery of angiogenic factors, such as vascular endothelial growth factor (VEGF), has been shown to provide modest improvement in wound healing. Here, the importance of specialty delivery systems is explored in controlling wound bed drug distribution and consequently improving healing rate and quality. Two intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Animal work has also been done with needles of a similar length and shown success at improving wound healing. [ 38 ] In the case of a chronic wound application, the shorter needles would target the epidermis while longer needles could penetrate into the dermis and release their payload into these deeper layers. As an example, longer needles could be loaded with VEGF‐containing hydrogels to deliver these biochemical cues to the existing vasculature in the dermis.…”
Section: Resultsmentioning
confidence: 99%
“…Animal work has also been done with needles of a similar length and shown success at improving wound healing. [ 38 ] In the case of a chronic wound application, the shorter needles would target the epidermis while longer needles could penetrate into the dermis and release their payload into these deeper layers. As an example, longer needles could be loaded with VEGF‐containing hydrogels to deliver these biochemical cues to the existing vasculature in the dermis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report used hollow MNs to continuously deliver VEGF intradermally and showed the effect of promoting angiogenesis and wound healing in animal experiments. 65 However, due to their poor mechanical strength, hollow MNs have the risk of fracture during use. 66 Dissolvable MNs are usually made of water-soluble polymers such as HA.…”
Section: Mnsmentioning
confidence: 99%
“…In vivo studies showed that VEGF delivery by miniaturized needles improved quality and healing rate, compared to the topically applied group. These effects were attributed to the distribution profile of VEGF through the miniaturized needles, affording a more uniform drug distribution through the wound area, and also a more accurate delivery to the target point, compared to the other methods [149].…”
Section: Peptides and Proteinsmentioning
confidence: 99%